2012
DOI: 10.1002/job.1795
|View full text |Cite
|
Sign up to set email alerts
|

The devil without and within: A conceptual model of social cognitive processes whereby discrimination leads stigmatized minorities to become discouraged workers

Abstract: In contrast to the substantial literatures on job loss, underemployment, and re-employment, management scholars have paid scant attention to "discouraged workers," defined as those who want to work but have ceased looking for work because of labor market-related reasons such as discrimination. Drawing together the labor economics category of discouraged workers, the diversity literature on employment discrimination, and social cognitive research on careers, we model social cognitive mechanisms whereby discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 123 publications
(156 reference statements)
0
40
0
2
Order By: Relevance
“…One explanation for these effects is that factors such as gender and race trigger discrimination within internal and external labor markets, which restricts these employees' access to secure jobs with better work designs (Heslin, Bell, & Fletcher, 2012;LaMontagne, Krnjacki, Kavanagh & Bentley, 2013). Discrimination by formal decision-makers then can continue once an individual is within a job.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for these effects is that factors such as gender and race trigger discrimination within internal and external labor markets, which restricts these employees' access to secure jobs with better work designs (Heslin, Bell, & Fletcher, 2012;LaMontagne, Krnjacki, Kavanagh & Bentley, 2013). Discrimination by formal decision-makers then can continue once an individual is within a job.…”
Section: Demographicsmentioning
confidence: 99%
“…Such biased task allocations can, in turn, affect perceptions of employees' competence, further perpetuating inequality in work design (Clegg & Spencer, 2007;Humphrey & Berthiaume, 1993). Stigmatization and marginalization can also lead disadvantaged groups to identify with their stigmatized identity, which interferes with personal resources such as self-efficacy (Heslin et al, 2012), which are crucial for negotiating i-deals to improve work design or craft one's job.…”
Section: Demographicsmentioning
confidence: 99%
“…16,17 However, persistent structural inequities and social advantage/ disadvantage promote learned helplessness 78 and entitlement/ privilege 79 among populations in ways that encourage some patients to believe they have fewer options and lower selfefficacy, and encourage others to believe they have more options and higher self-efficacy, regardless of the external realities. Structural inequality affects not only the material realities (e.g., proportion of goods and services available) of a person's life, but also the internal beliefs and expectations that may obscure perceptions of those material realities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found individual and family variability in the response to economic stress (Donnellan, Conger, McAdams, & Neppl, 2009;Fonesca et al, 2016) and the reaction or appraisal of stressful situations differs across ethnic minority groups (Heslin, Bell, & Fletcher, 2012;Tandon et al, 2013). The impact of ethnic minority group membership expresses itself through (a) the differential risk of stress, (b) the variation in the appraisal of stress, and (c) the effect of stress-mediating variables (Aranda & Knight, 1997).…”
Section: Introductionmentioning
confidence: 99%